Bandar Lampung General Election Commissions Strategies to Suppress Abstention in The 2024 Presidential Election (A Fiqh Siyasah Approach) - Gesti Rahayu, Tyas; Faizal, Liky; Santoso, Rudi (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
Law No. 7 of 2017 highlights that general elections enable citizens to express their sovereignty; however, the phenomenon of abstention (golput) indicates a decline in voter participation. This trend often results from a lack of trust in elected representatives, who are seen as failing to effect significant change. Rising abstention rates require urgent attention from organizers, especially the General Election Commission (KPU) of Bandar Lampung. From an Islamic legal perspective, abstention is deemed haram according to the Indonesian Ulema Council. This study employs qualitative methods through field research, including observation, interviews, and document collection. The KPU of Bandar Lampung has implemented various strategies to reduce abstention in the upcoming 2024 elections, guided by goal-setting, policy formulation, and plan development theories. This research aims to provide insights for enhancing voter participation.